(untitled) (ENTHYMEMA, 2020)
The text introduces the proceedings of the Workshop MOD, which took place in IULM University on 17-18 October 2019. The title of the event mentions the forty years distance underlying the different receptions, by different generations, of Calvino’s novel If on a Winter’s Night a Traveler. Nowadays, a writer-oriented interpretation substitutes a previous (and maybe necessary) reader-oriented interpretation. The peculiar ‘voice’ adopted by Calvino, moreover, is a critical and theorical issue, liable to be discussed in future essays.